Linear Operation to Quality Improvement Coal Image Using Contrast Stretching and Sobel - Muh. Yusuf; Hasni Kasim; Haslinda Haslinda; Rachmat Rachmat; Muh. Fahmi Basmar (International Journal Labs, 2023)
This linear operation is one way to improve image quality using contrast stretching and sobel methods. The processed image has a higher contrast value so that it can produce new information. This study aims to apply the contrast stretching method to improve the quality of coal images in JPEG format. Based on the test results, the average value of coal variance has increased. This result proves that contrast stretching causes the spread of RGB values to be even. The even distribution of RGB values causes the coal image to have better contrast than the original image before the repair. Where the results of the study found that the quality of coal was obtained based on the level of calorie content contained in coal, the smaller the calorie content, the quality of the stone was very good